Does Pre-operative Biliary Drainage Influence Long-Term Survival in Patients With Obstructive Jaundice With Resectable Pancreatic Head Cancer? - Shen, Ziyun; Zhang, Jun; Chen, Haoda; Wang, Weishen; Xu, Wei; Lu, Xiongxiong; Zhou, Yiran; Zhao, Shiwei; Xu, Zhiwei; Deng, Xiaxing; Wang, Jiancheng; Weng, Yuanchi; et al. (Frontiers in Oncology, 2020)
Objectives: Whether preoperative biliary drainage (PBD) affects long-term survival of patients with obstructive jaundice with pancreatic ductal adenocarcinoma (PDAC) who underwent pancreaticoduodenectomy is still controversial. Most of the previous research did not include the important total serum bilirubin (TB) level before intervention as well as before surgery. The aim of this study is to evaluate the impact of PBD on long-term survival after considering the TB level. Methods: Data were collected retrospectively from patients with obstructive jaundice who underwent resection of pancreatic head cancer in a high-volume center. X-Tile software and Kaplan-Meier survival analysis were applied to determine the optimal cut-off levels for TB and age based on the minimal probability (P) value and the largest χ2 value. Multivariate Cox regression analyses were performed after univariate analysis to assess independent prognostic factors for overall survival (OS) and disease-free survival (DFS). Results: Of 426 patients with obstructive jaundice who underwent pancreaticoduodenectomy for resectable pancreatic head cancer during a 7-year period, 242 (56.8 %) received PBD and 184 (43.2%) underwent surgery directly. The OS of patients who received PBD was significantly worse than that of patients who did not receive PBD by univariate analysis (median of 16.6 vs. 22.2 months, P = 0.048). After including liver function parameters in the multivariate Cox regression, we found that the use of PBD was not associated with OS or DFS, while TB before intervention > 150 μmol/L was an independent adverse prognostic factor for both OS (hazard ratio (HR), 1.42; 95% CI, 1.05–1.91) and DFS (HR, 1.38; 95% CI, 1.08–1.77). Conclusions: In patients with obstructive jaundice with resectable pancreatic head cancer, undergoing PBD before pancreaticoduodenectomy did not impair or benefit survival rates compared with surgery alone. However, TB before intervention > 150 μmol/L predicted an unfavourable prognosis, irrespective of the PBD procedure.